SOSIALISASI DAN PELATIHAN APLIKASI KEAMANAN PENGGUNAAN GADGET BAGI ANAK - Budianto, Heru; Aji Permana; Dede Irawan; Elsa Syakira; Acep Trian (Politeknik Negeri Sriwijaya, 2024)
Gadgets are one of the most widely used technological products at the moment along with the development of the internet. Gadgets are not only used by adults but children and even toddlers have used them. This is due to the effects of the Covid-19 pandemic and the rapid development of information and technology. Gadgets and the internet as technology products have positive and negative sides. The use of gadgets by children without supervision and regulation from their parents tends to have more negative impacts on children, both in terms of physical and mental health. Weak supervision and regulation of gadget use is present due to a lack of insight into the knowledge and competence of parents regarding parental control. Nangka Village, which is one of the villages in Kadugede District, Kuningan Regency, is one of the villages where most of the residents are familiar with and use technology. Parental control is something that is not widely known and understood so there are indications of the negative effects of gadgets on children. Based on the results of the analysis and discussion activities, it was found that there was a need for socialization and training on parenting control for parents in Nangka village